Epigenetic alteration at the DLK1-GTL2 imprinted domain in human neoplasia: analysis of neuroblastoma, phaeochromocytoma and Wilms' tumour - Dewi Astuti; Farida Latif; Kate Wagner; Dean Gentle; Wendy N. Cooper; Daniel Catchpoole; Richard G. Grundy; Anne C. Ferguson‐Smith; Eamonn R. Maher (2005)
Epigenetic alterations in the 11p15.5 imprinted gene cluster are frequent in human cancers and are associated with disordered imprinting of insulin-like growth factor (IGF)2 and H19. Recently, an imprinted gene cluster at 14q32 has been defined and includes two closely linked but reciprocally imprinted genes, DLK1 and GTL2, that have similarities to IGF2 and H19, respectively. Both GTL2 and H19 are maternally expressed RNAs with no protein product and display paternal allele promoter region methylation, and DLK1 and IGF2 are both paternally expressed. To determine whether methylation alterations within the 14q32 imprinted domain occur in human tumorigenesis, we investigated the status of the GTL2 promoter differentially methylated region (DMR) in 20 neuroblastoma tumours, 20 phaeochromocytomas and, 40 Wilms' tumours. Hypermethylation of the GTL2 promoter DMR was detected in 25% of neuroblastomas, 10% of phaeochromocytoma and 2.5% of Wilms' tumours. Tumours with GTL2 promoter DMR hypermethylation also demonstrated hypermethylation at an upstream intergenic DMR thought to represent a germline imprinting control element. Analysis of neuroblastoma cell lines revealed that GTL2 DMR hypermethylation was associated with transcriptional repression of GTL2. These epigenetic findings are similar to those reported in Wilms' tumours in which H19 repression and DMR hypermethylation is associated with loss of imprinting (LOI, biallelic expression) of IGF2. However, a neuroblastoma cell line with hypermethylation of the GTL2 promoter and intergenic DMR did not show LOI of DLK1 and although treatment with a demethylating agent restored GTL2 expression and reduced DLK1 expression. As described for IGF2/H19, epigenetic changes at DLK1/GTL2 occur in human cancers. However, these changes are not associated with DLK1 LOI highlighting differences in the imprinting control mechanisms operating in the IGF2-H19 and DLK1-GTL2 domains. GTL2 promoter and intergenic DMR hypermethylation is associated with the loss of GTL2 expression and this may contribute to tumorigenesis in a subset of human cancers.